Comparison between magnesium sulfate and dexmedetomidine in controlled hypotension during functional endoscopic sinus surgery - Bayram,Adnan (2015)
BACKGROUND AND OBJECTIVES: It is crucial to decrease bleeding during functional endoscopic sinus surgery. Our primary goal was to investigate the effects of magnesium sulfate and dexmedetomidine used for controlled hypotension on the visibility of the surgical site. METHODS: 60 patients aged between 18 and 65 years were enrolled. In the magnesium sulfate group (Group M), patients were administered 40 mg/kg magnesium sulfate in 100 mL saline solution over 10 min as the intravenous loading dose 10 min before induction, with a subsequent 10-15 µg/kg/h infusion during surgery. In the dexmedetomidine group (Group D), patients were administered 1 µg/kg dexmedetomidine in 100 mL saline solution as the loading dose 10 min before surgery and 0.5-1 µg/kg/h dexmedetomidine during surgery. Deliberate hypotension was defined as a mean arterial pressure of 60-70 mmHg. RESULTS: Bleeding score was significantly decreased in Group D (p = 0.002). Mean arterial pressure values were significantly decreased in Group D compared to that in Group M, except for the initial stage, after induction and 5 min after intubation (p < 0.05). The number of patients who required nitroglycerine was significantly lower in Group D (p = 0.01) and surgeon satisfaction was significantly increased in the same group (p = 0.001). Aldrete recovery score ≥9 duration was significantly shorter in Group D (p = 0.001). There was no difference between the two groups in terms of recovery room verbal numerical rating scale. CONCLUSIONS: Dexmedetomidine can provide more effective controlled hypotension and thus contribute to improved visibility of the surgical site.